Advances in Psychology Research. Volume 145 - Columbus, Alexandra (New York : Nova Science Publishers, Incorporated, 2021)
"This book includes eight chapters that detail recent advancements in psychology research. Chapter One aims to discuss the general identity concept and the specific concept of working identity through the lens of the tradition of the social psychology field and analyzes the limits and possibilities of conception constructions of these concepts in contemporary times, and also proposes portraits of the working identity constructions in the contemporary world. Chapter Two discusses the development of post-traumatic stress disorder following first-episode psychosis and involuntary hospitalization. Chapter Three explores the comorbidity of borderline personality disorder (BPD) and substance use disorders (SUD), identifying their epidemiological data and clarifying the functioning of borderline individuals, including their tendency to use substances. Chapter Four describes a type of cognitive behavioral therapy that is adapted to psychosis for treatment of schizophrenia. Chapter Five describes a group of patients with acute psychosis and their evolution over five years. Chapter Six provides an overview of jealousy as a function of Davis' sexual property proposition, framed using Lewin's Field Theory. Chapter Seven aims to explore the frequency and narrative of positive, neutral and negative perceptions of the accessibility, acceptability, and adequacy of the International Classification of Diseases 11th Revision depressive episode from the perspective of both those experiencing it and their primary relative caregivers. Lastly, Chapter Eight illustrates the discipline of social psychology through examples in the field of social influence, social norms and social representations."--
4.2.3.2. Management of Hallucinations -- 4.2.3.3. Management of Negative Symptoms -- 4.2.3.4. Management of thought Disorder -- 4.2.3.5. Group Therapy -- 4.2.4. Consolidation and Relapse Prevention -- 5. CBT in Patients with High Risk for Psychosis -- 5.1. Brief Report of the Screening and Management Protocol for UHR Patients -- 5.2. Ethical Considerations -- Conclusion -- References -- Biographical Sketch -- Chapter 5 -- Acute Psychosis Episodes and Evolution after Five Years. Sociodemographic Characteristics, Precipitating Factors, Diagnostic Evolution and Psychosocial Adjustment -- Abstract
WorldCat record variable field(s) change: 050, 082, 650
Keywords: Psychology -- Research; Electronic books